The Economic Impact Of Coronavirus To The Economic Fallout And The Education System Of The World - Burxanova Aziza Hamidovna (Journal of Geography, Regional Planning and Development, 2024)
The purpose of this study is to assess the pandemic's impact on the worldwide education system, including student participation declines, adult learning difficulties, and late enrollments. The research methodology that is used is devising educational solutions based on technology and increasing student capacity to strengthen the educational system against future crises. The study's conclusion is to recommend economic and educational reforms to policymakers and concerned citizens, with an emphasis on improving the economy and educational systems. This study's application is the use of technological and pedagogical solutions to support more rapid system development in education.